Agriculture curriculum needs of homeschooling parents: A case study - Kelber, LaKoda (My University, 2019)
The purpose of this study was to explore the gaps, if any, in the curriculum needs of homeschooling parents. It was motivated by the perception that parents homeschooling their children did not have official curriculum for agriculture or agricultural science subjects. The result of this was that the children were not getting the appropriate instruction in these subjects, depriving them of an important set of knowledge, especially since most of them grow up on farms. The research was originally intended to be a national study. However, time and resource constraints limited it to a few states in the Midwest. Therefore, the results reported in the study represent a case study of the situation and not a representation of the national situation. The study used a structured online survey on the Qualtrics® platform and a snowball sampling technique to collect information on homeschooling families and their agriculture and agricultural science curriculum needs. The response rate was low: 53 parents from mostly Iowa and Missouri (approximately 80% together) responded. Nearly three-quarters of the respondents had bachelor’s or advanced degree and about 41% indicated their spouses had at least a bachelor’s degree. These homeschooling parents were experienced in developing curriculum with about two-thirds of them having taught for at least five years. Majority of the parents indicated that they were motivated to homeschool their children by their need to spend more time with their children (69%) while almost half of them indicated the negative peer pressure in public schools motivated them. While more than 64% of respondents to the survey indicated they included agriculture and agricultural science in their education program, less than 17% of them said they had a formal curriculum. When asked if their homeschooled children incorporated farm work formally into their schoolwork, only 17% answered in the affirmative. The conclusion from the agriculture and agricultural science instruction is ad hoc when it is included in homeschooling program of the parents who responded to the survey. When asked if they saw a gap in their agriculture and agricultural science curriculum and whether they needed capacity enhancement, they answered in the negative. It hoped that this result is reflective of this small group of Midwest respondents and not of the broader homeschooling community. The suggestion, therefore, is that the research be expanded to encompass a larger representative sample to ascertain the observations from this case study.
Keywords: Homeschool; Agricultural Education; Agriculture Curriculum; Online Learning